Screening method for Staphylococcus aureus identification in subclinical bovine mastitis from dairy farms - Pumipuntu, Natapol (Vet World, 2017)
BACKGROUND: Staphylococcus aureus is one of the most important contagious bacteria causing subclinical bovine mastitis. This bacterial infection is commonly identified by determine the pathogen in bovine milk samples through conventional technique including coagulase test. However, this test has several disadvantages as low sensitivity, risk of biohazard, cost expensive, and limited preparation especially in local area. AIM: Aim of this study was to compare and assess the screening method, Mannitol fermentation test (Mannitol salt agar [MSA]), and deoxyribonuclease (DNase) test, for S. aureus identification in milk samples. MATERIALS AND METHODS: A total of 224 subclinical bovine mastitis milk samples were collected from four provinces of Thailand and determined S. aureus using conventional method and also subjected to the screening test, MSA and DNase test. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) among both tests were analyzed and compared to the tube coagulase test (TCT), as reference method. Immunological test by latex agglutination and molecular assay by determined spa gene were also used to identify and differentiate S. aureus. RESULTS: A total of 130 staphylococci were isolated by selective media, Gram-stain, and catalase test. The number of S. aureus which identified using TCT, MSA and DNase test were 32, 102, and 74 isolates, respectively. All TCT results were correlated to results of latex agglutination and spa gene which were 32 S. aureus. MSA showed 100% sensitivity, 28.57% specificity, 31.37% PPV, and 100% NPV, whereas DNase showed 53.13% sensitivity, 41.84% specificity, 22.97% PPV, and 73.21% NPV. DNase test showed higher specificity value than MSA but the test presented 26.79% false negative results whereas no false-negative result from MSA when comparing to TCT. CONCLUSION: MSA had a tendency to be a good preference for screening S. aureus because of its high sensitivity and NPV. The result from this study will improve a choice to use a screening test to diagnose S. aureus of veterinary field for prompt disease controlling and effective treatment.